Analysis of the effect of facilities, accessibility, promotion, and price on tourist trust and satisfaction through tourist loyalty as a mediation variable on halal tourism in surakarta city - Yustisiana Pramesti, Syifana Putri; Isa, Muzakar (Law and Economics, 2025)
This study examines the influence of accessibility, facilities, pricing, and promotion on tourist trust and satisfaction, with loyalty as a mediating factor in halal tourism in Surakarta City. Employing a quantitative approach, data were collected from 200 respondents through online questionnaires using a Likert scale. Purposive sampling was utilized to select participants meeting specific criteria. PLS-SEM was applied for data analysis due to its suitability for complex models. Findings reveal that competitive pricing, adequate facilities, seamless accessibility, and effective promotions significantly enhance satisfaction and loyalty, which, in turn, strengthen trust. Loyalty plays a crucial role in mediating these relationships. Destination managers should focus on infrastructure improvements, digital marketing, and service optimization based on periodic visitor evaluations. Future studies should explore the impact of cultural influences, environmental sustainability, and social media on tourist perceptions